A regionally verified method for fusion indexes of gas outbursts in adjacent seams within close coal seam groups - Zhang, Shuai (Frontiers in Earth Science, 2023)
To effectively solve the problem of regional verification of gas outbursts adjacent to close coal seam groups, a method of regional verification and index fusion of the working face was proposed to promote the general idea of advanced detection, index fusion, and the determination of the critical values, inspection, and verification. Based on the engineering background of Xiaotun Coal Mine and advanced geological exploration, drilled holes were arranged in key locations and consisted of small intervals between layers, thickened coal seams, and geological structural belts. Moreover, fusion indexes were selected according to the statistical analysis of laboratory tests and on-the-spot measurements, which can be used to determine that the critical value of the residual gas content of the fusion indexes of the six adjacent upper coal seams is 8 m3/t and K1 is 0.50 ml/g.min1/2. The results illustrate that the method for measuring residual gas content and the fusion index of the K1 value during the effect test of regional prevention measures is convenient and effective for advanced regional verification of adjacent coal seams, which can also provide a reference and guiding significance for the regional verification of adjacent coal seams of gas outbursts under similar conditions.